Koinōnia and Justice. From Republic to Parmenides - Gutiérrez, Raúl (2022)
The main reason why the developmental interpretation of the platonic Parmenides believes this dialogue constitutes a crisis in the development of Plato’s thought is the idea that the philosopher criticizes therein its Theory of Ideas of the middle period – Phaedo, Symposium, Republic. The theory supposedly criticized would conceive the Ideas as absolutely simple and isolated unities that, as such, would make impossible the fulfilment of their own function. This would only be possible by a new relational conception of the Ideas introduced in Parmenides and developed in Sophist. In contrast to some scholars who do not even mention certain passages in those dialogues (e.g. Cordero, 2014, 2016), I will show 1) that the notion of koinōnia is essential to the project of the Republic, since its central idea, the notion of justice, is unthinkable without the notion of koinōnia of the Ideas with each other; and 2) that Parmenides makes use of this notion of justice (150a) precisely in relation to the eidetical koinōnia (143a-b) and to the Idea conceived as a whole (ὅλον) “which has come to be one complete/perfect thing out of all its parts – ἐξ ἁπάντων ἓν τέλειον γεγονός” (157e1, ἓν ἐκ πολλῶν, 157c6, ἓν τέλειον μόρια ἔχον, 157e4).